Extractingthe Ethical Challenges of Pharmacy Profession in Iran, a Qualitative Study - Kourosh Delpasand (Journal of Research in Medical and Dental Science, 2018)
Pharmacy, like medicine, has been linked to the health and well-being of people and society and has had its ethical standards. Over the past few decades, pharmacy, especially in pharmaceutical services, has changed from a simple medical prescription to a relationship between pharmacist, patient and health care system. Regarding the place and influence of patient-pharmacist relationship on the health cycle and the lack of guideline, it is necessary to do such kind of study. In order to identify and explain the ethical issues and challenges, according to the opinion of pharmaceutical experts, an open interview was held with them. The interviewees were professors, who are familiar with the ethics of pharmacy faculties, medical ethics experts, members of board of directors of Iran pharmacists association, members of board of directors at Tehran pharmacists association, boards of directors of Iran pharmacists association, and a number of managers of Food and Drug Organization in Tehran and other cities in Iran. The literature was reviewed by the researcher and it was used as a guide to direct the interviews. The content analysis is done after writing down the content of interviews. In general, a conventional approach was used to analyze the obtained qualitative data, the interview text and the obtained information. Classes were extracted directly from textual data and a deep understanding of ethical challenge in pharmacy was obtained. The classes and clusters emerged during data collections. Finally, after numerous interviews, the results showed that the lack of familiarity with the ethics of pharmacy and the lack of trust in pharmaceutical companies are significant ethical challenges and problems.